The Use of Picture Cards to Elicit Postgraduate Dental Student Feedback - Peter Fine; Albert Leung; John Francis; Chris Louca (MDPI AG, 2018)
The aim of this study was to elicit information about the use of picture cards to stimulate student feedback following a postgraduate dental course. Twenty-nine general dental practitioners (GDPs) volunteered for the study. Following an explanation of how this style of feedback worked, students were asked to choose a picture card from those available and use that image to stimulate their feedback. An independent interviewer introduced the topic and gathered comments in the form of qualitative data, generated by pre-formed questions. 93% (n = 26) questionnaires were completed and returned. 77% (n = 20) GDPs reported enjoying giving their feedback by 'picture card' technique; 83% (n = 20) reported this form of feedback stimulated their thoughts. Qualitative data were analysed thematically. Some GDPs felt the picture cards helped them formulate their feedback, others felt being able to give feedback to a third party they did not know was beneficial and giving feedback as a group was helpful. This novel approach of using picture cards to stimulate feedback was well received by these GDPs. A mixed result as to the value of this style of feedback was evident. A group feedback session facilitated by a stranger was considered to be a valuable approach to take.